Analysis of Providing Employee Performance Allowances at the Sambas Class IB Religious Court from an Islamic Economic Perspective - Juniati; Zarul Arifin; Deni Irawan (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2023)
The purpose of this research is to determine and analyze the perceptions of Civil Servants at the Sambas Religious Court Class I B regarding the provision of performance allowances, the view of Islamic Economics towards the provision of performance allowances for Civil Servants at the Sambas Religious Court Class I B. This type of research uses field research. which uses qualitative descriptive data, namely research whose data is extracted through observations. The data sources in this research are Civil Servants of the Sambas Religious Court Class I B. The data collection methods used are interviews, documentation, reference searches. Data management and analysis collection techniques were carried out by conducting in-depth interviews with informants. The results of this research show that the provision of performance allowances to Civil Servants of the Sambas Class I B Religious Court has mostly experienced an increase in performance and level of discipline which can be seen from two aspects, namely attendance and monthly performance reports. And most of them are in accordance with Islamic views, this is because the allowances given are in accordance with employee performance. The implication of this research is that Civil Servants of the Sambas Religious Court Class I B should increase supervision of their employees so that they pay more attention to their duties and responsibilities so that the implementation of employees' main duties and functions can run well. Therefore, employees should use benefits as motivation for working.